2015
DOI: 10.1016/j.scitotenv.2015.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Assessing determinants of maternal blood concentrations for persistent organic pollutants and metals in the eastern and western Canadian Arctic

Abstract: Aboriginal peoples in the Canadian Arctic are exposed to persistent organic pollutants (POPs) and metals mainly through their consumption of a traditional diet of wildlife items. Recent studies indicate that many human chemical levels have decreased in the north, likely due to a combination of reduced global chemical emissions, dietary shifts, and risk mitigation efforts by local health authorities. Body burdens for chemicals in mothers can be further offset by breastfeeding, parity, and other maternal charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…As an example with high seafood consumption country like Korea, Sakamoto et al has reported that the mean maternal RBCs level of lead and mercury were 26.4 ng/g and 9.41 ng/g from Japanese women [ 23 ]. Additionally, high levels of mercury and methylmercury in pregnant women and children were also observed in studies from the Mediterranean [ 24 ] and Arctic region [ 25 ].…”
Section: Discussionmentioning
confidence: 82%
“…As an example with high seafood consumption country like Korea, Sakamoto et al has reported that the mean maternal RBCs level of lead and mercury were 26.4 ng/g and 9.41 ng/g from Japanese women [ 23 ]. Additionally, high levels of mercury and methylmercury in pregnant women and children were also observed in studies from the Mediterranean [ 24 ] and Arctic region [ 25 ].…”
Section: Discussionmentioning
confidence: 82%
“…Geographic differences in OC levels as observed likely also reect history, socioeconomic, culture, physiological factors, lifestyle and dietary differences. 22,24,[41][42][43] Age as a positive predictor of serum OC concentrations and parity and previous breastfeeding as negative ones are well understood. 35,44 Because of the relatively long half-lives (in years) of OCs (typically > 7 years), 45 body burdens increase over time.…”
Section: Factors Inuencing Oc Concentrationsmentioning
confidence: 99%
“…While the number of studies examining the impacts of environmental pollution upon IPs is growing (Brugge and Gobble 2002; Curren et al 2015), most of this research is isolated and fragmented across disciplines and geographic regions. Few efforts have cut across disciplinary topics or regions (e.g., pollution in Arctic traditional foods [Kuhnlein and Chan 2000]; water, sanitation, and IPs [Jiménez et al 2014]), and there is no global review that maps out the worldwide impacts of environmental pollution on IPs.…”
Section: Introductionmentioning
confidence: 99%